Práticas interdisciplinares em currículo de letramento digital: conexão entre vida e trabalho - Leite, Joice Lopes (2019)
Technology advances in all sectors of contemporary society, linked to economics, politics, health, culture and education. We live in a time of global action of both local and regional impacts, a scenario in which the advent of the internet becomes easily accessible to all people, transforming their way of living, learning and teaching. This dissertation incorporates a research based on the methodology of life history and the interdisciplinary perspective that enables the sharing of practices that facilitate the elaboration of a digital literacy curriculum. The research was carried out in the daily life of Basic Education schools in the city of São Paulo, where the experience of implementing the Digital Literacy Curriculum mediated by the use of New Technologies of Information and Communication as mediating instrument of teaching and learning processes occurred. The research was developed with the objective of analyzing interdisciplinary experiences lived by the researcher and interpreting the meanings of teaching and learning in the process of Digital Literacy articulating the interpretations to the delimited conceptual theoretical base. The theoretical foundations were set with emphasis on works by authors such as Paulo Freire, Ivani Catarina Arantes Fazenda and Seymour Papert. Interdisciplinarity stands out in this process for its innovative nature and conducive to the development of daring attitudes towards knowledge, in order to involve students and educators in the protagonism of their own history as subjects responsible for humanization and transformation through education. Also noteworthy are the results of the analysis of the perception of the importance of the connections established in the course of academic and professional activities which enabled the understanding of how humans relate, the need for self-knowledge, reflection on the practice and the importance of love as a reference for life, in a world increasingly connected in information and disconnected from people